Molecular Origins of Functional Diversity in Benzylisoquinoline Alkaloid Methyltransferases - Morris, Jeremy S.; Facchini, Peter J. (Frontiers in Plant Science, 2019)
O- and N-methylations are ubiquitous and recurring features in the biosynthesis of many specialized metabolites. Accordingly, the methyltransferase (MT) enzymes catalyzing these modifications are directly responsible for a substantial fraction of the vast chemodiversity observed in plants. Enabled by DNA sequencing and synthesizing technologies, recent studies have revealed and experimentally validated the trajectories of molecular evolution through which MTs, such as those biosynthesizing caffeine, emerge and shape plant chemistry. Despite these advances, the evolutionary origins of many other alkaloid MTs are still unclear. Focusing on benzylisoquinoline alkaloid (BIA) producing plants such as opium poppy, we review the functional breadth of BIA N- and O-MT enzymes and their relationship with the chemical diversity of their host species. Drawing on recent structural studies, we discuss newfound insight regarding the molecular determinants of BIA MT function and highlight key hypotheses to be tested. We explore what is known and suspected concerning the evolutionary histories of BIA MTs and show that substantial advances in this domain are within reach. This new knowledge is expected to greatly enhance our conceptual understanding of the evolutionary origins of specialized metabolism.